Improving the Human Resource Capacity of Journal Managers through Open Journal Systems (OJS) Training - Semara, I Made Trisna; Saputra, I Putu David Adi; Chandra, I Made Krisna Adi (Jurnal Abdi Masyarakat, 2026)
The Vocational Innovation Product Business Implementation Program is proposed to optimize the potential for financial independence (revenue generating) of vocational higher education institutions through the commercialization of academic expertise in the field of scientific publication management. Although the institution has demonstrated its superior capacity in managing Open Journal Systems (OJS), such as successfully accelerating the accreditation ranking of internal journals significantly at the national level, this technical expertise is currently still documented as a cost center for fulfilling the tridharma obligations. The main problem faced is that the capacity of human resources managing these systems has not yet been standardized towards commercial services, and there is not yet a prototype of a paid service system capable of absorbing the high publication demands from researchers outside the institution. As a solution, this program introduces the innovation of forming a "Professional Publication Service and OJS Clinic Unit" through business management training for academic service journal managers. The strategic added value of this innovation is its implementation, which embraces the Teaching Factory concept integrated with the Tourism Research Methods course. The methodological weakness of incoming external client manuscripts will be restructured and anonymized to serve as empirical case study material in class, so that students do not merely learn tourism research theory, but are trained in analytical sharpness akin to professional editors. The activity plan is executed through three measured stages: 1) Preparation, which includes the formulation of Standard Operating Procedures (SOP) for academic service businesses and the determination of tariff schemes; 2) Implementation, consisting of technical guidance on OJS commercialization, integration of digital payment systems, service simulations, and the launch of business prototypes; 3) Evaluation, involving operational assistance for paid transactions and measurement of customer satisfaction. Mandatory and additional output targets include: the establishment of a prototype commercial academic publication service system that is independent, obtaining copyright protection for SOP/governance modules, publication of articles in service journals, releases in electronic mass media, commercial unit profile videos, and updating the Semester Learning Plan (RPS) for the Tourism Research Methods course.